Risk factors for venous ulcer following ACUTE venous thromboembolism: Results from the RIETE Registry - Jean-Philippe Galanaud; Laurent Bertoletti; Paolo Prandoni; Pedro Gallego; Daniela Mastroiacovo; Lucia Mazzolai; Angel Samperiz; Yacine Rabah; Nuria Ruiz-Gimenez; Marija Zdraveska; Susan R Kahn; Manuel Monreal (My University, 2015)
Background: Venous ulcer, the most serious consequence of chronic venous insufficiency (CVI), is associated with a high morbidity, impaired quality of life and high costs. To date, risk factors for venous ulcer after acute VTE have not been characterized. Objective: To identify independent predictors of venous ulcer development one year after an acute VTE event. Methods: Using data from the RIETE international registry, we analysed risk factors for venous ulcers in patients with an objectively confirmed symptomatic acute VTE (DVT and/or pulmonary embolism (PE)) and followed up for at least one year. During follow-up, signs and symptoms of CVI, occurrence of a venous ulcer in the leg ipsilateral to DVT or, in the absence of reported DVT, in any leg were reported by local investigators. Independent predictors of venous ulcers were assessed using a stepwise multivariable model. Results: Of the 34,144 patients included in the RIETE registry, 4,305 were recruited in centres participating in long-term (1 to 3 years) follow-up. Of these, 54% (n=2,337) underwent an assessment for CVI. After a mean (SD) follow-up of 383 (+/-575) days, 55% (n=1297) had signs or symptoms of CVI and 2.5% (n=59) had developed a venous ulcer. History of previous VTE (OR=4.4 [2.6 - 7.7], signs of venous insufficiency (i.e. leg varicosities) at time of VTE event (OR=2.3 [1.3 - 4.0]), diabetes (OR=2.0 [1.0 - 3.8]), obesity (OR=1.8 [1.1 - 3.2]) and male sex (OR=2.7 [1.5 - 4.9]) were independent predictors of an increased risk of venous ulcer. Conversely, older age, presence of an objectively confirmed DVT at study enrolment, anticoagulant duration (<1 vs. >1 year), anticoagulant type (extended low molecular weight heparin vs. vitamin K antagonist), or presence of vena cava filter had no significant impact on risk of venous ulcer. When restricting our analysis to the 1790 patients with objectively confirmed DVT only, results remained similar in magnitude. Proximal character of DVT was associated with a 30% non-significant increased risk of - unquestionable - post-thrombotic ulcer but the proportion of distal DVT was low in our population (11%). Conclusions: After an acute VTE event, history of VTE, pre-existing signs of CVI, male sex, diabetes and obesity independently influenced the risk of venous ulcer. VTE therapeutic management (neither duration nor drugs) did not appear to modify this risk. Our results suggest that clinicians should consider strategies aimed to prevent ulcers in high risk patients, such as preventing VTE recurrence, use of compression stockings in those with CVI and encouraging weight loss in obese patients.